THE RELATIONSHIP BETWEEN TEACHER INVOLVEMENT IN CURRICULUM DEVELOPMENT AND STUDENT LEARNING OUTCOMES - Asep Kusmawan; Rashid Rahman; Nina Anis; Opan Arifudin (International Journal of Educatio Elementaria and Psychologia, 2025)
Teacher involvement in curriculum development plays a critical role in shaping effective teaching strategies and fostering meaningful learning experiences. However, limited participation of teachers in curriculum design processes often results in less relevant and engaging instructional practices, potentially impacting student learning outcomes. This study examines the relationship between teacher involvement in curriculum development and student achievement in elementary schools. A correlational research design was employed, involving 120 elementary school teachers and their corresponding student groups. Data were collected using teacher participation surveys, curriculum alignment evaluations, and student learning outcome assessments. The findings revealed a significant positive correlation between teacher involvement in curriculum development and student learning outcomes. Teachers who actively participated in designing curriculum elements tailored to their students’ needs demonstrated higher effectiveness in instructional delivery, resulting in improved academic performance and engagement among students. The research concludes that increasing teacher involvement in curriculum development is essential for enhancing student learning outcomes and recommends integrating collaborative curriculum design practices at the institutional level.